PENGARUH SURPLUS ARUS KAS BEBAS TERHADAP MANAJEMEN LABA DENGAN KUALITAS AUDITOR SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia dan Bursa Malaysia Tahun 2015) - Muhammad Iqbal; Darsono Darsono (Diponegoro Journal of Accounting, 2020)
This study aims to examine the effect of free cash flow surpluses on earnings management with auditor quality as a moderating variable. Surplus free cash flow as an independent variable, earnings management as the dependent variable measured through discretionary accruals and auditor quality as a moderating variable. This research uses leverage and company size as control variables.The type of data used in this study is secondary data and involves 216 manufacturing sector companies in Indonesia and Malaysia. The sample selection method in this study uses a purposive sampling technique with the criteria of companies listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange that publish annual reports in 2015. The analysis technique used is multiple regression analysis.This study uses agency theory to formulate two hypotheses that lead to the results of the analysis. The results showed that free cash flow surplus had a positive effect on earnings management practices, and auditor quality could moderate the relationship between free cash flow surplus and earnings management. This shows that the availability of free cash flow in the company will encourage earnings management practices and good auditor quality can reduce earnings management.